Emerging Nanocarriers-based Approaches to Diagnose and Red uce Vascular Inflammation in Atherosclerosis - Calin, Manuela; Manduteanu, Ileana (Current Medicinal Chemistry, 2017)
Exploitation of nanotechnology advances in the cardiovascular medicine has led to new approaches for the diagnosis and therapy of vascular inflammation associated to cardiovascular diseases. Innovative nanoparticles targeted to the main players in the arterial wall inflammation in atherosclerosis (i.e. inflammatory molecules, immune or resident cells) have been already developed to diagnose and/or reduce excessive vascular inflammation and is eagerly awaited that promising preclinical and early clinical results to boost the approval of the first nanocarrier in this field. This review discusses the challenges and the steps undertaken so far to produce powerful multifunctional nanoparticles capable of raising new scenarios for future precision medicine in atherosclerosis.
Keywords: nanoparticles